2021
DOI: 10.1016/j.mad.2021.111540
|View full text |Cite
|
Sign up to set email alerts
|

Senescence and senolytics in cardiovascular disease: Promise and potential pitfalls

Abstract: Highlights Studies have demonstrated that senescence contributes to the pathophysiology of several age-related cardiovascular diseases. Senolytics eliminate senescent cells in cardiovascular tissues and prevent or reverse disease progression. While this data is encouraging, questions remain regarding the potential short and long-term detrimental effects of senolytic mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 181 publications
0
73
0
Order By: Relevance
“…However, these complications and alterations are potentially rare, especially with prolonged use, daily treatment and high doses as in the treatment of chronic myelogenous leukemia. They include prolongation of the QT interval, arrhythmia and palpitations [ 56 ]. On the other hand, low-dose Dasatinib was found to ameliorate hypertrophic cardiomyopathy progression [ 57 ] so that the use of Dasatinib in low dose and short time is relatively safe.…”
Section: Discussionmentioning
confidence: 99%
“…However, these complications and alterations are potentially rare, especially with prolonged use, daily treatment and high doses as in the treatment of chronic myelogenous leukemia. They include prolongation of the QT interval, arrhythmia and palpitations [ 56 ]. On the other hand, low-dose Dasatinib was found to ameliorate hypertrophic cardiomyopathy progression [ 57 ] so that the use of Dasatinib in low dose and short time is relatively safe.…”
Section: Discussionmentioning
confidence: 99%
“…However due to variations in patient responsiveness to treatment owing to the multifactorial nature of atherosclerosis, which results in weak regenerative potential, continuous efforts are needed to provide anti-atherogenic agents with varied mechanisms of action. Targeting SC populations appeared as a valuable strategy since many studies have demonstrated that senescence contributes to the pathophysiology of several age-related including CVDs [ 233 , 234 ]. It was recently reported that senolysis reverses aging phenotype in cardiovascular disorders.…”
Section: Established and Emerging Therapeutical Strategies For Atherosclerosismentioning
confidence: 99%
“…It was recently reported that senolysis reverses aging phenotype in cardiovascular disorders. Generating therapies targeting elimination of SCs or senoprotective pathways would inhibit the progression of undesirable features of aging, and become promising therapies for CVDs [ 234 ].…”
Section: Established and Emerging Therapeutical Strategies For Atherosclerosismentioning
confidence: 99%
“…Recently, a new approach has been developed using nanocapsules whose cargo are senolytic drugs (specific and unspecific) in mice to deliver to the senescent cells [ 157 ]. In this regard, senotherapy was used to treat senescent cells’ accumulation in CVD, preventing disease evolution [ 160 ]. In this sense, preclinical studies have focused on preventing or reversing a wide range of aging and premature aging diseases, CVD associated-CKD, using senolytic drugs [ 160 ].…”
Section: Unraveling Underlying Mechanisms: Therapeutical Approachesmentioning
confidence: 99%
“…In this regard, senotherapy was used to treat senescent cells’ accumulation in CVD, preventing disease evolution [ 160 ]. In this sense, preclinical studies have focused on preventing or reversing a wide range of aging and premature aging diseases, CVD associated-CKD, using senolytic drugs [ 160 ]. However, the field is still new, and before administrating these drugs to humans, clinical trials shall be conducted.…”
Section: Unraveling Underlying Mechanisms: Therapeutical Approachesmentioning
confidence: 99%